Temperature change and the total stress anomaly in paste backfill - Alsidqi, Hasan; Ting, Wee Kiet; Fauzan, Sahdi; Siti Noor Linda, Taib; Norsuzailina, Mohamed Sutan; Badhrulhisham, Abdul Aziz; Andy, Fourie (GEOMATE International Society, 2018)
This paper presents preliminary results from a laboratory backfill model test in order to explain the effect of temperature change during the cement hydration on the total stress within cemented paste backfill. It is conducted via temperature control test in the absence of the cement. This investigation is an attempt to resolve an anomalous behavior reported in recent full scale monitoring reports, where the total vertical stress at the stope base shows a progressive increase after backfilling is terminated. The result in this paper shows that the total vertical stress is not affected by the level of the temperature but rather by the temperature gradient. The empirical relationship between the temperature gradient and the change in the total vertical stress is proposed. The total stress anomaly found in the full scale monitoring of paste backfill could be explained by the finding. © 2018, Int. J. of GEOMATE.